Predicting Airborne Infection Risk: Association Between Personal Ambient Carbon Dioxide Level Monitoring and Incidence of Tuberculosis Infection in South African Health Workers . (26th March 2022) - Nathavitharana, Ruvandhi R; Mishra, Hridesh; Sullivan, Amanda; Hurwitz, Shelley; Lederer, Philip; Meintjes, Jack; Nardell, Edward; Theron, Grant
Abstract: Background: High rates of tuberculosis (TB) transmission occur in hospitals in high-incidence countries, yet there is no validated way to evaluate the impact of hospital design and function on airborne infection risk. We hypothesized that personal ambient carbon dioxide (CO2 ) monitoring could serve as a surrogate measure of rebreathed air exposure associated with TB infection risk in health workers (HWs). Methods: We analyzed baseline and repeat (12-month) interferon-γ release assay (IGRA) results in 138 HWs in Cape Town, South Africa. A random subset of HWs with a baseline negative QuantiFERON Plus (QFT-Plus) underwent personal ambient CO2 monitoring. Results: Annual incidence of TB infection (IGRA conversion) was high (34%). Junior doctors were less likely to have a positive baseline IGRA than other HWs (OR, 0.26; P = .005) but had similar IGRA conversion risk. IGRA converters experienced higher median CO2 levels compared to IGRA nonconverters using quantitative QFT-Plus thresholds of ≥0.35 IU/mL ( P < .02) or ≥1 IU/mL ( P < .01). Median CO2 levels were predictive of IGRA conversion (odds ratio [OR], 2.04; P = .04, ≥1 IU/mL threshold). Ordinal logistic regression demonstrated that the odds of a higher repeat quantitative IGRA result increased by almost 2-fold (OR, 1.81; P = .01) per 100 ppm unit increase in median CO2 levels, suggesting a dose-dependent response. Conclusions: HWs face high occupational TB risk. Increasing median CO2 levels (indicative of poor ventilation and/or high occupancy) were associated with higher likelihood of HW TB infection. Personal ambient CO2 monitoring may help target interventions to decrease TB transmission in healthcare facilities and help HWs self-monitor occupational risk, with implications for other airborne infections including coronavirus disease 2019. Abstract : Health workers in countries like South Africa face a high occupational tuberculosis (TB) risk. Increasing average personal ambient carbon dioxide (CO2 ) levels were associated with higher likelihood of TB infection. CO2 monitoring may help target interventions to decrease TB transmission in health facilities.